Application of Stem in Improving Mastery of Mathematics Concept of Speed Materials at Elementary School Grade (Class) V - Abas, Sirojudin; Agustin, Mubiar; Rahman, Rahman; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
STEM is an approach that has recently become a hot topic to be discussed among academics, because STEM is believed to be able to solve problems that students will face in order to prepare themselves in 21st century life. The purpose of this study is to examine how far students have increased mastery of mathematical concepts after given STEM. In this study involved 25 students consisting of 9 male students and 16 female students. The method used is Classroom Action Research (PTK) by using 10 test item descriptions and data collection instruments using observation sheets and lesson plans. This study was conducted with the II cycle, from the initial data known to the number of students which completed a total of 13 students and who have not completed 12 students. After the action in cycle I with STEM The result showed an increase, which is 18 students that completed and who have not completed 7 students, then in cycle II that completed 21 students and who have not completed 4 students. After the students receive the learning treatment using STEM The research showed that there is an increase in the mastery of mathematical concepts marked by the achievement of Minimum Criteria Submission (KKM) stipulated in class V is 70. Thus, the implementation of STEM in mathematics learning at class V speed material at Cimanggung State Elementary school III can improve the mastery of student concept